Temporal Relationship between Action Potential and Ca2+ Transient in Characean Cells - Kikuyama, Munehiro; Tazawa, Masashi (Plant and Cell Physiology, 1998)
Temporal relationship between the action potential and the change in cytosolic Ca2+ concentration was investigated in cells of four species of Characeae, Chara corallina, Nitellopsis obtusa, Nitella flexilis and Nitella axilliformis . The Ca2+ transient was detected by light emission from Ca2+-sensitive photoprotein aequorin injected into the cytoplasm. Action potential was triggered by an outward or sometimes inward electric current pulse of 20–50 ms in most cases. In all species the action potential started at almost the same time as the time at which the light emission from aequorin began to increase. Also the peak of action potential almost coincided with that of light emission, which is in contrast with the slower Ca2+ transient in Chara reported by Thiel et al. [(1997) J. Exp. Bot. 48: 609]. A discussion was made on the origin of Ca2+ transient and the ionic processes during membrane excitation.